Risk of eating disorder in Colombian women who go to the gym - Jorge Emiro Restrepo; Tatiana Castañeda Quirama (Interacciones)
Background: Mental health in gyms has not been a topic of study in Colombia. Social stereotypes of beauty and dissatisfaction with body image make women a population prone to excessive exercise. This research analyzes the risk of eating disorder in women who attend gyms (comparing ages), its relationship with the frequency of physical exercise and the use of diet to improve physical appearance. Methods: 519 women with ages between 15 and 50 years participated. The EAT-26 Eating Attitude Test was used, a standardized procedure to estimate the frequency of physical exercise and a brief socio-demographic survey. Results: the percentages of women with risk (46.8%) of TBI and without risk (53.2%) are similar, the factor scores and the total of the EAT-26 only show significant differences in the age range 15 -19 and 20-24, no significant correlations were found between the factors and the total score of the EAT-26 and the measure of frequency of physical exercise, and there is an association between the risk of eating disorders and diet to improve physical image. Conclusion: The percentage of women at risk for eating disorders is higher than those reported for high school students, university students, and athletes. A very high percentage of gym users would be compromising their mental health in some way, considering the frequency values ​​of physical exercise.